Answer:
The two numbers are
518
694
Step-by-step explanation:
As per requirements the two equations will be
X+Y=1212
X-Y=518
When we subtract these equations we get
X=1212-518
X=694
Now put the X value and find the Y value in any equation
X+Y= 1212
Y=1212-X
Where X = 694
Y=1212-694
Y=518
X=694 and Y=518
Formula= (y2-y1)/ (x2-x1)
(-5 - -1) / (-2 - -4)
(-4) / (2) = -2
q8 is C
(-3 - -3) / (8 - 4)
(0) / (4) = 0
q12 is D
Answer:
-13, -3
15, 2.6
Step-by-step explanation:
x, y are the numbers
x = 5y + 2
x×y = 39
(5y + 2)×y = 39
5y² + 2y - 39 = 0
the solution of a quadratic equation :
y = (-b ± sqrt(b² - 4ac))/2a
a = 5
b = 2
c = -39
y = (-2 ± sqrt(2² - 4×5×-39))/2×5 =
= (-2 ± sqrt(4 + 780))/10 =
= (-2 ± sqrt(784))/10 = (-2 ± 28)/10
y1 = (-2 + 28)/10 = 26/10 = 2.6
y2 = (-2 - 28)/10 = -30/10 = -3
x1 = 5×2.6 + 2 = 13 + 2 = 15
x2 = 5×-3 + 2 = -15 + 2 = -13
The value of the expression 4(5² - 3 - 2x)² is <u>576</u>.
In the question, we are asked to evaluate the expression 4(5² - 3 - 2x)², where x = 5.
To find the value of the expression, we find the value of each term with the value assigned to the variable and then put back the terms in the expression to get the final value.
The term 5² = 25.
The term 2x, when x = 5, can be shown as 2x = 2*5 = 10.
Taking the terms back to the expression, we get:
4(5² - 3 - 2x)²
= 4(25 - 3 - 10)²
= 4(12)²
= 4(144)
= 576.
Thus, the value of the expression 4(5² - 3 - 2x)² is <u>576</u>.
Learn more about solving expressions at
brainly.com/question/723406
#SPJ9